Web Recommendation Using Microblogging Information - Lakshmi Prasanna, U; Revathi, A (International Journal of Computer Sciences and Engineering, 2025)
As of late, the gap between online business and person to person communication has turned out to be m ore and more indistinct. Numerous online businesses reinforce the social sign in system where customers can sign-in on their portals by applying their informal organization characters, like their Twitter or Facebook IDs. Users additionally can announce their recently bought items on social networking or microblogs by mentioning the corresponding product url from the online business sites. In this paper, we put forward an innovative solution for “cross site cold start web product recommendation” to endorse different items from “e-commerce” sites for users at “microblogging or social networking” sites in “cold start positions”, a very rare concept explored before. The foremost task is to utilize the information fetched from microblogging or social interacting. In exact, we propose learning the two client and items element depictions called client embeddings and item embeddings respectively from the information fetched through online commercial sites using “recurrent neural systems”. And later applying “Altered Gradient boosting trees” model to convert user long range informal statement keywords into user embedding’s. We at that point build up a component based “Lattice factorization method” which can be used to learn client embedding’s for “cold-start product recommendation”.